Synthetic Genomics From a Yeast Perspective - Koster, Charlotte C.; Postma, Eline D.; Knibbe, Ewout; Cleij, Céline; Daran-Lapujade, Pascale (Frontiers in Bioengineering and Biotechnology, 2022)
Synthetic Genomics focuses on the construction of rationally designed chromosomes and genomes and offers novel approaches to study biology and to construct synthetic cell factories. Currently, progress in Synthetic Genomics is hindered by the inability to synthesize DNA molecules longer than a few hundred base pairs, while the size of the smallest genome of a self-replicating cell is several hundred thousand base pairs. Methods to assemble small fragments of DNA into large molecules are therefore required. Remarkably powerful at assembling DNA molecules, the unicellular eukaryote Saccharomyces cerevisiae has been pivotal in the establishment of Synthetic Genomics. Instrumental in the assembly of entire genomes of various organisms in the past decade, the S. cerevisiae genome foundry has a key role to play in future Synthetic Genomics developments.